2014
DOI: 10.4103/0976-7800.127792
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the cervix with foci of malignant melanoma

Abstract: Introduction:Sarcomatoid squamous cell carcinoma (SSCC) is a rare malignancy of the cervix. Until date around eighteen cases of SSCC have been reported in the literature. It is an aggressive tumor with poor prognosis. The tumor usually presents at an advanced stage. Similarly, primary melanomas of the uterine cervix are rare tumors with not more than 60 cases reported in the world literature. It also has a poor prognosis. There is no reported case of sarcomatoid carcinoma with malignant melanoma. Here, we are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, only two reports have discussed the MRI or PET features of USC in the literature [ 11 , 12 ]. Shrivastava et al found that USC showed hyperintensity on T2WI and isointensity on T1WI similar to cervical mass lesions with extra-uterine extension [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only two reports have discussed the MRI or PET features of USC in the literature [ 11 , 12 ]. Shrivastava et al found that USC showed hyperintensity on T2WI and isointensity on T1WI similar to cervical mass lesions with extra-uterine extension [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two reports have discussed the MRI or PET features of USC in the literature [ 11 , 12 ]. Shrivastava et al found that USC showed hyperintensity on T2WI and isointensity on T1WI similar to cervical mass lesions with extra-uterine extension [ 11 ]. Milind et al described abnormal FDG accumulation of USC in the region of the cervix and the upper vagina by PET, with maximum SUVs of 5.7 and 10.6 for the vagina and the cervix, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of cases with mucosal melanoma frequently present as large polypoid masses, this system is of little use in disease staging [ 2 ]. As a result, the International Federation of Gynecology and Obstetrics (FIGO) staging system has prevailed among authors and has been widely applied, since it correlates better with prognosis and survival and given the similar clinical presentation and pattern of spread of PMMC and cervical adenocarcinoma [ 5 , 8 , 24 , 28 , 34 , 37 , 47 ].…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…Due to the lack of recommendations and specific guidelines, most patients with PMMC are usually treated according to the treatment protocols established for cervical squamous cell carcinoma [ 47 ]. Surgical treatment usually consists of total or radical hysterectomy with or without bilateral salpingo-oophorectomy (RAH/TAH+BSO), usually combined with or without pelvic lymphadenectomy (LND) and/or partial-superior vaginectomy (PV).…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
See 1 more Smart Citation